2019
DOI: 10.1080/00380253.2019.1593063
|View full text |Cite
|
Sign up to set email alerts
|

Victim or Villain? Racial/Ethnic Differences in News Portrayals of Individuals with Mental Illness Killed by Police

Abstract: As a social problem, little is known about how individuals are portrayed in the news when race/ethnicity and mental illness intersect. This is important because of the ability of news to influence perceptions and policies about mental illness across race/ethnicity. This article examines how individuals with mental illness who were killed by police during 2015 and 2016 were portrayed in the news. Content analysis of 301 online news articles indicates that stereotypes associated with mental illness were diÄerent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Finally, almost none of the outlets used graphic images of Brown's body lying in the street. This was surprising to us given how much that image circulated on social media, the local outrage about the slow response to his death (Hill 2016), and research that shows that graphic images of police violence are more likely to be included in media accounts when the victim is Black (Frankham 2017). We…”
Section: Picturing Michael Brownmentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, almost none of the outlets used graphic images of Brown's body lying in the street. This was surprising to us given how much that image circulated on social media, the local outrage about the slow response to his death (Hill 2016), and research that shows that graphic images of police violence are more likely to be included in media accounts when the victim is Black (Frankham 2017). We…”
Section: Picturing Michael Brownmentioning
confidence: 94%
“…Media coverage of policing (and more recently, police violence) has long been a critical site in the struggle over racial ideologies (Frankham 2017;Hattery and Smith 2017;Hughey 2015;Owusu-Bempah 2016;Ward 2018). Osagie K. Obasogie and Zachary Newman (2016), for example, find that mainstream journalists have traditionally deferred to the law enforcement perspective, criminalizing the victims of police violence (see also Araiza et al 2016;Stone and Socia 2019).…”
Section: Race and Racism In The News: Constructing Police Violencementioning
confidence: 99%
“…A third core contribution of this article is to identify a new framing, “Dying on the Streets,” which has received less attention in recent work focused on the nexus of mental illness and violence (Frankham 2020; McGinty et al 2014). The frame accentuates concerns about homeless people articulated in the “Excessive De-institutionalization” frame and partly displaces the safety concerns about “Dangerous Brain Diseases.” As in discussions of the opioid epidemic, this frame “medicalizes” rather than “criminalizes” drug use and disruptive behavior (Netherland and Hansen 2017; Shachar et al 2020).…”
Section: Conclusion: Rewriting the Magna Cartamentioning
confidence: 99%
“…Fourth, negative, stereotypical elements about the victims’ lifestyles. Furthermore, a study that examined how individuals with mental illness who were killed by police were portrayed in the news revealed that mental illness is particularly emphasized in news reports about White people with mental illness, and less so in news reports about African American or Hispanic people with mental illness (Frankham, 2020).…”
Section: Portrayal Of Race In Crime Mediamentioning
confidence: 99%